Developing a regional environmental information system based on macro-level waste indicators. (June 2015) - Cifrian, Eva; Andres, Ana; Viguri, Javier R.
Graphical abstract: Highlights: Novel methodology to obtain sets of waste indicators with different objectives. Indicators to provide a comparative analysis of the situation of waste. Indicators to assess the achievement of waste management policy objectives. Indicators to analyze the relation of socio-economic variables on waste generation. Use of an aggregated index to the temporal evolution of regional waste sector. Abstract: Waste information is necessary for proper management planning. However, data on waste generation and management are sometimes not reliable enough, do not exist or are not useful for the sector. This is due to the high number of waste types and flows, and actors (producers, managers and administrations), which make data collection and treatment difficult. Furthermore, data loss occurs because some waste flows have economic value and return to the second-hand markets without monitoring. The development of a waste information system for a region is more than just about establishing a routine data collection on waste. It is a way to support the challenges of decision-making on waste management. These challenges range from strategic issues of waste management in the national government to the basic challenges of running local governments. In the Cantabrian region, three indicator sets were defined to constitute the waste information system: (a) a Basic Indicator Set, which provides an overview of the status of the generation and management of the main waste streams, giving a national and international comparative analysis of the situation; (b) a Specific Indicator Set, which monitors the objectives of the different waste policies, and (c) a Transverse Indicator Set, which analyses the influence of different economic and social variables on the generation of specific waste streams. The Waste Information System of the Cantabrian Region has been created using a specific methodology for developing indicator sets with multiple objectives. This methodology consists of seven steps: (i) the synthesis, selection of the indicators sets; (ii) analysis of the system under study and data sources; (iii) evaluation of the indicators proposed; (iv) application and interpretation; (v) public review, dissemination and updating protocol; (vi) improvement of indicators sets using SWOT analysis; and (vii) aggregation of all indicators in an aggregated index. These indicator sets with a total of 27 indicators allow tracking the evolution of generation and management of waste streams and the achievement of the policy objectives, establishing a data record, evaluating the data and sources of data, monitoring proposed action and its effectiveness summarizing large amounts of data on waste in order to spread it to the public and finally, aggregate all information in a single index that allows the evaluation of the evolution of all waste sectors in time.